Syntactic Agreement in English Grammar : A Palatable Hub for African Development: A Study of Students in Alvan Ikoku Federal College of Education, Owerri - Ifeyinwa Juliana Umeh; Chioma Winner Onyeama; Florence Ebere Ubah (International Journal of Global Sustainable Research, 2025)
Syntactic agreement in English grammar is relatively imperative and it is a powerful linguistic element. Its useful and significant roles make impact in everyday usage both in written and spoken English as it greatly affects second language users of English. The paper is geared towards highlighting the meaning of syntactic agreement and some of the numerous types of syntactic agreement. Specifically, the study dwells more on the rules governing subject verb agreement. It brings to light the purpose and relevance of subject verb agreement. It also projects to discuss how syntactic agreement poses problems to the second language users of English. Copious local and international literature were reviewed. Principles and parameters theory by Chomsky (1981) and Binarity principle by Mbah (2016) were the theories that anchor this study. In principles and parameters, Chomsky’s claims that human grammars are constructed entirely of principle, not of rules because rules are construction specific but principles are universal, with some degree of parameterization. Binarity principle relies more on the principle of constituent commanding. This implies that, the head of a construction determines the type of verb it will take. Two research questions were used. 100 students from 3 schools in Alvan Ikoku Federal College of Education, Owerri, were sampled using structural questionnaire. The results of the data were analyzed using simple percentages. The findings reveal that students were not conversant with the use of subject verb agreement. We recommend that great attention should be paid to the nuances of grammar, especially with regard to subject verb agreement